Hubungan fraksi area trabekula anterior mandibula dengan kepadatan tulang lumbar spine untuk deteksi dini osteoporosis - Sri Lestari; Rini Widyaningrum (Majalah Kedokteran Gigi Indonesia, 2017)
The relationship of anterior mandible trabecular area with bone mass density of lumbar spine for early detection of osteoporosis. Bone mineral density is an indicator of osteoporosis, including the bone mineral density of lumbar spine. The decrease of lumbar spine bone mass density will cause an alteration in another site, including the mandibular. The aim of this research is to determine the predictor of lumbar spine bone mineral density using trabecular bone image of anterior mandible on periapical radiographs. The research was conducted by extracting the area fraction at mandible trabecular bone using digital periapical radiograph from 25 subjects. Canny edge detection was used in digital image processing for each radiograph. The regions of interest were selected from the image obtained by canny edge detection, so that the area fraction could be measured. A linier regression test was applied to determine a relationship between the area fractions of mandible trabecular bone with the bone mineral density of lumbar spine. The result of linear regression test showed that the area fraction of mandible trabecular bone had a moderate negative correlation with bone mass density of lumbar spine (α = 0.046; R = -0.403). The direction of the correlation was negative (b = -0.145). The area fraction of mandible trabecular bone on periapical radiographs could be used as the predictor for bone mass density of lumbar spine.ABSTRAKKepadatan tulang merupakan indikator osteoporosis, salah satu diantaranya adalah kepadatan tulang pada lumbar spine. Penurunan kepadatan tulang pada lumbar spine mempengaruhi kondisi tulang lain, termasuk tulang rahang bawah (mandibula). Tujuan penelitian ini adalah untuk menentukan prediktor densitas mineral tulang menggunakan citra radiograf periapikal tulang trabekula pada regio anterior rahang bawah. Penelitian dilakukan dengan ekstraksi fraksi area tulang trabekula mandibula yang tercitrakan pada radiograf periapikal digital dari 25 subjek. Pengolahan citra digital pada radiograf periapikal dilakukan dengan menggunakan metode deteksi tepi canny terhadap masing-masing citra radiograf. Region of Interest diseleksi dari citra hasil deteksi canny, sehingga dapat dilakukan pengukuran fraksi area. Uji regresi linier dilakukan untuk mengetahui hubungan antara nilai fraksi area trabekula mandibula dengan tingkat kepadatan tulang pada lumbar spine. Hasil uji regresi linier menunjukkan bahwa nilai fraksi area trabekula mandibula berkorelasi negatif dengan kepadatan tulang dengan kekuatan sedang (α = 0,046; R = -0,403). Adapun arah korelasi antara nilai fraksi area trabekula mandibula dengan kepadatan tulang adalah negatif (b = -0,145). Fraksi area tulang trabekula pada citra radiograf periapikal dapat digunakan sebagai prediktor kepadatan tulang pada lumbar spine.